INDIRA GANDHI -------A NON-CABINET FIGURE PRIME MINISTER - Associate Professor Madona Kebadze (Scholar Express Journal, 2022)
There are many outstanding people in world history. There are many strong, independent and successful women who have made a name for themselves in history and their work will be remembered for generations to come. I will talk about Indira Gandhi as such a strong woman.
Keywords: strong; remembered; work; woman